Transcriptome Dynamics in the Developing Larynx, Trachea, and Esophagus - Wendt, Kristy D.; Brown, Jared; Lungova, Vlasta; Mohad, Vidisha; Kendziorski, Christina; Thibeault, Susan L. (Frontiers in Cell and Developmental Biology, 2022)
The larynx, trachea, and esophagus share origin and proximity during embryonic development. Clinical and experimental evidence support the existence of neurophysiological, structural, and functional interdependencies before birth. This investigation provides the first comprehensive transcriptional profile of all three organs during embryonic organogenesis, where differential gene expression gradually assembles the identity and complexity of these proximal organs from a shared origin in the anterior foregut. By applying bulk RNA sequencing and gene network analysis of differentially expressed genes (DEGs) within and across developing embryonic mouse larynx, esophagus, and trachea, we identified co-expressed modules of genes enriched for key biological processes. Organ-specific temporal patterns of gene activity corresponding to gene modules within and across shared tissues during embryonic development (E10.5-E18.5) are described, and the laryngeal transcriptome during vocal fold development and maturation from birth to adulthood is characterized in the context of laryngeal organogenesis. The findings of this study provide new insights into interrelated gene sets governing the organogenesis of this tripartite organ system within the aerodigestive tract. They are relevant to multiple families of disorders defined by cardiocraniofacial syndromes.